Progression of postural control and gait deficits in Parkinson's disease and freezing of gait: A longitudinal study. (July 2016) - Vervoort, Griet; Bengevoord, Aniek; Strouwen, Carolien; Bekkers, Esther M.J.; Heremans, Elke; Vandenberghe, Wim; Nieuwboer, Alice
Abstract: Background and aims: The relationship between impaired postural control and freezing of gait (FOG) in Parkinson's disease (PD) is still unclear. Our aim was to identify if postural control deficits and gait dysfunction progress differently in freezers compared to non-freezers and whether this relates to FOG development. Methods: 76 PD patients, classified as freezer (n = 17) or non-freezer (n = 59), and 24 controls underwent a gait and postural control assessments at baseline and after 12 months follow-up. Non-freezers who developed FOG during the study period were categorized as FOG converters (n = 5). Gait was analyzed during walking at self-preferred pace. Postural control was assessed using the Mini-BESTest and its sub-categories: sensory orientation, anticipatory, reactive and dynamic postural control. Results: Mini-BESTest scores were lower in PD compared to controls (p < 0.001), and in freezers compared to non-freezers (p = 0.02). PD has worse anticipatory (p = 0.01), reactive (p = 0.02) and dynamic postural control (p = 0.003) compared to controls. Freezers scored lower on dynamic postural control compared to non-freezers (p = 0.02). There were no baseline differences between converters and non-converters. Decline in postural control was worse in PD compared to controls (p = 0.02) as shown by a greater decrease in the total Mini-BESTest score. Similar patterns were found in freezers (p = 0.006), who also showed more decline in anticipatory (p < 0.001) and dynamic postural control (p = 0.02) compared to non-freezers. FOG converters had a greater decline in the total Mini-BESTest (p = 0.005) and dynamic postural control scores (p = 0.04) compared to non-converters. Gait outcomes showed no significant differences in any of the analyses. Conclusion: FOG is associated with more severe decline in postural control, which can be detected by the clinical Mini-BESTest. Highlights: PD patients with FOG show more severe balance decline than those without. Balance decline in patients with FOG occurs in absence of gait decline. Progression in balance dysfunction is related to the development of FOG. The Mini-BESTest is able to detect balance decline in the context of FOG. Balance decline is independent from motor progression and cognitive decline.